Principal component analysis of yield associated traits under abiotic stress conditions in Indian mustard (Brassica juncea) genotypes (Journal of Oilseed Brassica, 2026)
A study was carried out using 80 different genotypes and five check varieties, viz., NRCHB-101, RH-749, Giriraj, RH-406 and Kranti of Indian mustard in augmented randomized complete block design, for two Rabi seasons during 2020-22, under timely sown, drought and terminal heat stress conditions to determine the selection criteria among yield related traits. The cluster analysis, revealed that the first seven principal components (PC) in all three trials had eigenvalues more than 1 and contributed around 74, 75 and 72 % of variability in timely sown, drought and late sown conditions, respectively. The maximum contribution towards variation in timely sown condition was exhibited by biological yield, yield per hectare, plant height and yield per plant. The maximum contribution towards variability under drought sown condition was exhibited by number of siliquae per plant, number of secondary branches and plant height. Biological yield, yield per plant and plant height contributed maximum towards variability under late sown condition. Thus, the aforementioned traits should be considered for improving yield per plant under different conditions studied.